Aplikasi Irigasi Tetes (Drip Irrigation) dengan Berbagai Media Tanam pada Tanaman Pakcoy (Brassica rapa L.) - Arjuna Neni Triana; Rahmad Hari Purnomo; Ratna Juwita (Seminar Nasional Lahan Suboptimal, 2018)
Triana et al, 2019. Application of Drip Irrigation using Variety of Growing Media on Pakcoy (Brassica rapa L.). pp. 236-241.The purpose of this research was to determine the effects of irrigation water quantity level and growing media on water content, growth pakcoy (Brassica rapa L.) and water use efficiency using drip irrigation.systems. The method used in this research was Random Group Factorial Design using two factors which were the irrigation water quantity level and the growing media with three repetitions. The observed parameters were water content, water use efficiency, temperature, relative humidity, plant height, number of leaves and stover weight. The reseach result showed that the pakcoy plant best water use efficiency was at A3B4 treatment (irrigation water quantity 110 % with growing media compound ultisol soil, chorcoal husk and fertilizer fern) which was 4.351 kg/m3 with 104.67 grams wet pakcoy plant stover and the most inefficient pakcoy plant water use was at A1B1 treatment (irrigation water quantity 90 % with growing media compound ultisol soil, and husk charcoal) with water use efficiency was 1.351 kg/m3 and 27.33 grams wet pakcoy plant stover.